Economic impacts of small, medium and large agricultural-based sectors - Utit, Chakrin (2016)
Growth in final demands does not bring considerable implications on structural changes and growth of the agriculture sector in Malaysia. The current macroeconomic models are unable to provide explicit answer to this issue because they ignore the dualities in production technologies. The major limitation of the current macroeconomic models is production sectors are aggregative and thus homogeneity biases underlying in the models could not be avoided. In particular, one might get a false impression that development in some sector will “trickle down” equally to benefit all sectors in particular the agriculture sector. To tackle this issue, what is needed is a systematic methodological approach that links the different dualistic production structures and for this reason, input-output approach is used. This study has two objectives. First, it develops a new dataset for macroeconomic models that split the production sectors according to sizes— small, medium and large sectors. The new dataset which is termed as the IO TECH is also the biggest contribution from this study. Second, using the new dataset, it analyzes the key drivers for upstream and downstream agricultural SMEs and large sized agricultural-based sector. Results indicate that growth linkages between agricultural SMEs and large agricultural-based sector with other large sized sector in the production chain are weak—with the growth stimuli mostly benefitted the large sized sector. Among all of the agricultural-based sectors regardless of their sizes, the Oils and Fats sector and Food Products sector are identified as the main key drivers.